Problem-Oriented Gamification: Enhancing Creative Thinking Through the Electrical Monster Invaders Game - Valencia Fidelia Soetra; Nadi Suprapto; Adrian Bagas Damarsha; Indri Maya Ariana; Khofifatur Risma Faradillah; Muhammad Ghiyats Naufal; Husni Mubarok; Alif Syaiful Adam (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Physics education continues to face challenges due to students’ low levels of creative thinking skills (CTS) and the limited integration of problem-solving with gamification approaches in electromagnetic induction material. The research aims to describe significant differences in students’ CTS following problem-oriented gamification (POG) instruction supported by Electrical Monster Invaders (EMI), as well as students’ responses to the instruction. This research uses a quantitative experimental design involving one experimental class and two replication classes. Data collecting through CTS tests and student response questionnaires, analyzed using partial least squares structural equation models (PLS-SEM) to identify patterns of relationships among variables. The results indicate that POG-assisted learning using EMI effectively and consistently enhances CTS across all groups. Improvements were observed in every indicator. Structural analysis explains that POG plays a dominant role in shaping CTS, while the EMI serves as a supporting medium with an acceptable level of model fit. This study confirms that integration of problem-based learning, gamification, and interactive media is a relevant innovative strategy for enhancing CTS in physics learning (PL).